An assessment of thermocline-control methods for packed-bed thermal-energy storage in CSP plants, Part 2: Assessment strategy and results. (15th January 2019) - Geissbühler, L.; Mathur, A.; Mularczyk, A.; Haselbacher, A.
Highlights: The thermocline-control methods described in Part 1 are assessed using simulations. The assessment includes a stand-alone storage and a storage integrated in a CSP plant. Thermocline-control methods increased storage utilization factors significantly. Thermocline-control methods increased the annual averaged plant efficiency. Of the methods assessed in this work, the mixing method is the most promising. Abstract: Three thermocline-control (TCC) methods are assessed through numerical simulations for a thermal-energy storage (TES) filled with a packed bed of rocks. Two previously suggested methods are based on extracting or injecting heat-transfer fluid (HTF) through ports, while the third is a novel method based on mixing HTF streams. The assessment was carried out using simulations with a model that resolves the packed bed in one dimension. Simulations of stand-alone TES with maximum allowed outflow temperature differences of 10% at quasi-steady conditions showed that the mixing method with three ports led to the largest utilization factors – the fraction of the maximum storage capacity that is actually utilized – of 90.8 % and 85.1 % for molten salt (MS) and compressed air (CA) as HTF, respectively. These represent relative improvements of 38.8 % and 73.4 % compared to the baseline configurations without TCC. The increased utilization factors come at the expense of small decreases in the cycle exergy efficiency. For the mixing method with three ports, the exergy efficiencies were 97.3 % and 95.6 % for MS and CA, respectively. Simulations of a TES with MS as HTF integrated into a CSP plant operating on a Rankine steam cycle showed that TCC increases the annually averaged plant efficiency and the annual net electricity generated solely from thermal energy supplied by the TES. These results suggest that the small decreases in the exergy efficiency of the TES are outweighed by the large increases in the utilization factor.